Efficiency Enhancement in Plasmonic Dye-Sensitized Solar Cell Employing High Performance TiO2 Photoanode Doped with Silver Nanoparticles - Nasr, Nazia; Sayyad, Muhammad Hassan; Elbohy, Hytham; Qiao, Qiquan (International Journal of Sustainable Energy and Environmental Research, 2018)
High performance TiO2 photoanodes undoped and doped with silver nanoparticels of size about 15 nm were fabricated. Employing these electrodes dye-sensitized solar cells (DSSCs) were fabricated using N719 dye as sensitizer and iodide-triodide as redox couple. Current-voltage measurements were performed under the illumination of 100 mW cm-2 (AM 1.5). The electrical parameters of the fabricated cells were extracted from the current-voltage data that include open-circuit voltage, short-circuit current, shunt resistance, series resistance, fill-factor, ideality factor and solar energy-to-electricity conversion efficiency. The comparison of parameters revealed improvement in both the photovoltaic and electrical parameters of the plasmonic cell. The conversion efficiency measured for the reference cell without Ag NPs in TiO2 was 7.43 %, whereas the efficiency of plasmonic device with TiO2:Ag NPs was 9.26 %, resulting an overall efficiency improvement of 23% with Ag NPs. The increased performance of the plasmonic DSSC can be assigned to the improvement of its photovoltaic and electrical parameters. The improved short-circuit photocurrent density appears to be boosted due the enhanced light harvesting capability of the photoanode caused by the localized surface plasmon resonance effect induced in Ag nanoparticles. While, the rise in Voc can be credited to the upward shift of Fermi level of TiO2 due to the dopping of Ag nanoparticles in TiO2 network.